Tumor-associated macrophage-derived CXCL8 could induce ERα suppression via HOXB13 in endometrial cancer. Issue 1 (28th June 2016) - Tong, Huan; Ke, Jie-Qi; Jiang, Fei-Zhou; Wang, Xiao-Jun; Wang, Fang-Yuan; Li, Yi-Ran; Lu, Wen; Wan, Xiao-Ping
Highlights: TAMs downregulated ERα expression in human endometrial cancer cells. CXCL8 secreted by TAMs mediated the loss of ERα. TAM-derived CXCL8 induced ERα loss via HOXB13. Loss of ERα could promote endometrial cancer cells invasion. TAMs highly infiltrated in ERα-negative EC samples and indicated poor outcome. Abstract: Purpose: To elucidate the role of tumor-associated macrophage (TAM) in the loss of ERα in endometrial cancer (EC) and the underlying mechanism. Materials and methods: Tissue microarrays and immunohistochemistry assays were performed using endometrial cancer tissue along with coculture, immunofluorescence, invasion assays and ChIP-qPCR using a human endometrial cancer cell line. Results: Compared with normal tissue, an increased number of TAM was found in EC tissue (34.0 ± 2.6 vs. 8.3 ± 1.1, respectively; p < 0.001), which may downregulate ERα (27.4%, p < 0.05 for HEC-1A and 16.9%, p < 0.05 for Ishikawa) and promote EC cell invasion (1.8-fold, p < 0.001 for HEC-1A and 2.0-fold, p < 0.001 for Ishikawa). Furthermore, we found that TAM-derived CXCL8 mediated the loss of ERα and cancer invasion via HOXB13. HOXB13 was highly expressed in the ERα-negative subtype (r = −0.204, p = 0.002) and low expression of ESR1 was associated with a poor prognosis for EC patients (log-rank p < 0.05). Conclusion: TAM-secreted CXCL8 downregulated the ERα expression of EC cells via HOXB13, which may be associated with cancer invasion, metastasis and poor prognosis.